Gene Expression Changes and Anti-proliferative Effect of Noni (Morinda Citrifolia) Fruit Extract Analysed by Real Time-PCR - Hermansyah Hermansyah; Susilawati Susilawati (Universitas Jenderal Soedirman, 2017)
To elucidate the anti-proliferative effect of noni (Morinda citrifolia) fruit extract for a Saccharomyces cerevisiae model organism, analysis of gene expression changes related to cell cycle associated with inhibition effect of noni fruit extract was carried out. Anti-proliferative of noni fruit extract was analyzed using gene expression changes of Saccharomyces cerevisiae (strains FY833 and BY4741).Â Transcriptional analysis of genes that play a role in cell cycle was conducted by growing cells on YPDAde broth medium containing 1% (w/v) noni fruit extract, and then subjected using quantitative real-time polymerase chain reaction (RT-PCR).Â Transcriptional level of genes CDC6 (Cell Division Cycle-6), CDC20 (Cell Division Cycle-20), FAR1 (Factor ARrest-1), FUS3 (FUSsion-3), SIC1 (Substrate/Subunit Inhibitor of Cyclin-dependent protein kinase-1), WHI5 (WHIskey-5), YOX1 (Yeast homeobOX-1) and YHP1 (Yeast Homeo-Protein-1) increased, oppositely genes expression of DBF4 (DumbBell Forming), MCM1 (Mini Chromosome Maintenance-1) and TAH11 (Topo-A Hypersensitive-11) decreased, while the expression level of genes CDC7 (Cell Division Cycle-7), MBP1 (MIul-box Binding Protein-1) and SWI6 (SWItching deficient-6) relatively unchanged. These results indicated that gene expression changes might associate with anti-proliferative effect from noni fruit extract. These gene expressions changes lead to the growth inhibition of S.cerevisiae cell because of cell cycle defect.